Long-Term Outcomes of Pediatric Enterovirus Infection in Taiwan: A Population-Based Cohort Study - Tseng, Jui-Ju; Lin, Chien-Heng; Lin, Ming-Chih (Frontiers in Pediatrics, 2020)
Background The major burden of diseases in childhood has shifted from infectious diseases to chronic health conditions in recent decades. Although the rates of infectious diseases have decreased, the incidence of chronic diseases stemming from infectious agents continues to grow. Enterovirus is a major infectious disease of childhood and has been linked to numerous chronic diseases. We analyzed population-based data from Taiwan’s National Health Insurance Research Database (NHIRD) to investigate the correlations between enterovirus infection and major chronic health conditions in children. Methods Children diagnosed with enterovirus (EV) infection during 1999-2003 were identified from the Longitudinal Health Insurance Database 2000 (LHID 2000), a subdataset of Taiwan’s National Health Insurance Research Database (NHIRD). A total of 14,168 patients were selected after excluding patients with existing chronic diseases and missing data. Another 14,168 patients matched by age and sex were selected as the control group. Five primary outcomes, including attention deficit and hyperactivity disorder (ADHD), epilepsy, asthma, allergic rhinitis, and atopic dermatitis, were recorded. Results The risks of ADHD, asthma, allergic rhinitis, and epilepsy were significantly increased in the EV group compared with the control group. The risk of atopic dermatitis was significantly increased in the crude model. However, there were no significant differences in the adjusted model. The risks of ADHD, asthma, allergic rhinitis, and epilepsy were also significantly increased in patients with severe EV infection compared with patients with non-severe EV infection. [Is this what you mean? If you are just comparing patients with and without EV infection, you have already mentioned this finding in the first sentence of the results.] Conclusion Chronic diseases, such as ADHD, epilepsy, and allergic diseases were shown to be associated with enterovirus infection during childhood. EV infection during early childhood might have long-term public health implications and thus prevention strategies should be implemented.